English-Vietnamese translation of taxation terminology = Dịch thuật ngữ Anh-Việt về thuế - Bùi, Thị Hòa (2021)
Recently, tax has been one of the key fields which impacts on the sociodevelopment of each nation. With the development of international trade, EnglishVietnamese translation of taxation documents and relevant materials has received an ever-increasing demand for. Though accounting for only small percentage of the whole text‟s length, new terms always need to be mastered first if the translator wants to have a perfect translation. However, not many researches on this topic have been conducted which offers the researcher a chance to study about translation procedures of English-Vietnamese taxation terminology. To make this study possible, both quantitative and qualitative approaches have been exploited. Firstly, quantitative approach is used to collect English tax terms and Vietnamese equivalents. On the base of data collection with a bank of tax terms, qualitative approach is employed to analyse data. With the above mentioned background, purposes and methodology, the study has revealed that only six common translation procedures are used to deal with tax terms. They are through translation, shift, modulation, cultural equivalence, functional equivalence and expansion. Through translation is the most dominant procedure applied in the translation of tax term whereas functional equivalence is the least one. Illustrations are given to clarify the findings of the study. The results of the research can help translators apply appropriate translation procedures in the translation of taxation terminology. Furthermore, it will benefit the researchers who are interested in the subject.